Star formation and AGN feedback in the local universe: combining LOFAR and MaNGA - Mulcahey, Celia R.; Leslie, Sarah K.; Jackson, Thomas M.; Young, J. E.; Prandoni, I.; Hardcastle, M. J.; Roy, N.; Małek, K.; Magliocchetti, M.; Bonato, M.; Röttgering, H. J. A.; Drabent, A. (Astronomy and astrophysics, 2022)
The effect of active galactic nuclei (AGN) on their host galaxies - in particular their levels of star formation - remains one of the key outstanding questions of galaxy evolution. Successful cosmological models of galaxy evolution require a fraction of energy released by an AGN to be redistributed into the interstellar medium to reproduce the observed stellar mass and luminosity function and to prevent the formation of over-massive galaxies. Observations have confirmed that the radio-AGN population is energetically capable of heating and redistributing gas at all phases, however, direct evidence of AGN enhancing or quenching star formation remains rare. With modern, deep radio surveys and large integral field spectroscopy (IFS) surveys, we can detect fainter synchrotron emission from AGN jets and accurately probe the star-forming properties of galaxies, respectively. In this paper, we combine data from the LOw Frequency ARray Two-meter Sky Survey (LoTSS) with data from one of the largest optical IFS surveys, Mapping Nearby Galaxies at Apache Point Observatory (MaNGA), to probe the star-forming properties of 307 local (z < 0.15) galaxies that host radio-detected AGN (RDAGN). We compare our results to a robust control sample of non-active galaxies that each match the stellar mass, redshift, visual morphology, and inclination of a RDAGN host. We find that RDAGN and control galaxies have broad star-formation rate (SFR) distributions, typically lie below the SFMS, and have negative stellar light-weighted age gradients. These results indicate that AGN selected based on their current activity are not responsible for suppressing their host galaxies’ star formation. Rather, our results support the maintenance mode role that radio AGN are expected to have in the local Universe.
Gesehen am 15.12.2022